The Constitution, the law, and freedom of expression, 1787-1987 - Stewart, James Brewer; Burger, Warren E., 1907-1995.; Macalester College; Wallace Conference on "the Constitution, Freedom of Expression, and the Liberal Arts" 1986 : Macalester College) (Carbondale : Southern Illinois University Press, 1987)
Contributions to the 1st Wallace Conference on "The Constitution, Freedom of Expression, and the Liberal Arts," held in Sept. 1986 at Macalester College ; sponsored by the college.
A house with many mansions: categories of speech under the first amendment / Antonin Scalia -- The need for a new Enlightenment: lessons in liberty from the eighteenth century / Norman Dorsen -- Freedom of expression as a gendered phenomenon / Mary Beth Norton -- The new psychology of human survival / Robert Jay Lifton -- The chemistry revolution and the media: freedom and responsibility / Harry B. Gray -- Talking in tongues: the writer and the state / John Edgar Wideman.
Contributions to the 1st Wallace Conference on "the Constitution, Freedom of Expression, and the Liberal Arts," held in Sept. 1986 at Macalester College; sponsored by the college.
Includes bibliographical references.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Freedom of speech -- United States -- History -- Congresses; Freedom of the press -- United States -- History -- Congresses; Liberté d'expression -- États-Unis -- Histoire -- Congrès.; Liberté de la presse -- États-Unis -- Histoire -- Congrès.; POLITICAL SCIENCE -- Government -- Judicial Branch; LAW -- Legal Services; LAW -- Civil Procedure; LAW -- Constitutional; LAW -- Public; Freedom of the press -- United States -- History; Freedom of speech -- United States -- History; Freedom of speech; Freedom of the press; United States; Liberté d'expression -- États-Unis -- Histoire -- Congrès.; Liberté de la presse -- États-Unis -- Histoire -- Congrès.; Freedom of speech -- United States -- History -- Congresses; Freedom of the press -- United States -- History -- Congresses; The Chris Fritz Comparative and Historical Legal Perspectives Collection (CHLP); Conference papers and proceedings; History; proceedings (reports); Conference papers and proceedings; Actes de congrès.